PERANCANGAN SISTEM BERBASIS WEB PEMBELAJARAN BAHASA JEPANG DENGAN TEMA SERAH TERIMA AKTIVITAS - Khoerudin, Ikna; Irma Purnamasari, Ade (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
This research explores the Japanese language with a focus on the theme of activity handover. The Japanese language is unique in its use of various characters such as kanji, hiragana, katakana, and romaji. The influence of Japanese popular culture such as anime and manga has sparked many people who want to learn Japanese. The ability to speak foreign languages, especially Japanese, is considered important for children's future. However, learning Japanese has its challenges, especially in understanding the three typefaces, namely hiragana, katakana, and kanji. To master the Japanese language, learners need to pay attention to various aspects such as vocabulary, grammar, conversation, reading, writing, and listening. In the context of the handover theme this activity involves the use of particles, verbs, and nouns. This research emerged as a solution to the imbalance between the number of students and Japanese language teachers at LPK IHMI Cirebon. By analyzing student growth data, it is necessary to create a web-based learning system for Japanese language learning with the theme of handover activities using the waterfall method with several stages, namely system engineering, needs analysis, design, coding, testing, and maintenance. Thus, this research produced a Japanese language learning system with the theme of handover activities in an interesting and interactive manner. This system is expected to be an effective solution to increase the understanding and motivation of Japanese language learners at LPK IHMI Cirebon.